Influence of knowledge, organisation culture and perceived characteristics of brand support behaviour policy mediated by social media adoption among microenterprise employees in Malaysia - Halil, Nur Afni (2022)
Social media is proven to provide a competitive advantage to organisations such as customer relations and service enhancement, cost reduction in marketing and customer service, improved information sharing and accessibility, improved brand visibility, and generated revenue. Nevertheless, organisations are prone to lose control over the dissemination of information through social media. Hence, the organisations will face potential risks, namely human error, processes, reputational, operation, regulatory compliance, and financial and information security. This study examined the influence of knowledge, organisation culture and perceived characteristics of the policy, which are the factors of social media policy adoption and also sought to explain the consequences of the adoption towards brand support behaviour among microenterprises employees in Malaysia. The study's objective was to analyse the direct effect of knowledge, organisation culture and perceived characteristics of policy towards brand supposocial media adoption among microenterprise employees in Malaysia rt behaviour and the mediating effect of adoption of social media policy between knowledge, organisation culture, and perceived characteristics of policy towards brand support behaviour. The underpinning theory used to develop the framework was based on Roger's Diffusion of Innovation Theory. A total of 203 datasets were employed for the final analysis. SPSS and SmartPLS (Partial Least Squares-Structural Equation Modelling) were used in performing the analysis. All hypotheses are supported by the analysis results except two, which were rejected. The study confirmed the direct relationship between knowledge and organisation culture and the adoption towards brand support behaviour. Furthermore, this study established the mediating effect of adoption between knowledge and organisation culture on brand support behaviour. However, the perceived characteristics were insignificant to both direct and indirect relationships. The study also discusses the theoretical and practical contributions as well as the limitations of the study and recommendations for future research. This paper contributes to sustainability literature by developing a theoretical model that reflects brand support behaviour in the specific context of microenterprises employees. These findings also assist policymakers among microenterprises and SMEs in improving social media policy or strategies to manage their social media effectively. Therefore, this study suggests that it is vital for an organisation to consider adopting social media policy as it has contributed to brand support behaviour among employees.